Evolutionary emergence of purposive goals and values a naturalistic teleology - Crosby, Donald A. (SUNY Press, 2023)
Where do the purposes, values, and existential meanings of the world come from? For many, they are conferred on the world and on humans within the world by a supernatural, transcendent, personal divine creator and sustainer. For others, they result from a God or divine presence residing within nature. For still others, they give evidence of mind and spirit as primordial principles suffusing nature from the outset and in all of its forms. In Evolutionary Emergence of Purposive Goals and Values, Donald A. Crosby takes issue with each of these views. His thesis is that mind, meaning, purpose, and value come into existence with the evolutionary emergence of life, and that evolution itself gives evidence of the creative power of two primordial natural principles: matter-energy and time. There is no overarching purpose, value, or meaning of nature as such, but there is a plethora of such factors evident in the evolved life forms of nature here on earth. This fact is especially evident in the day-to-day experiences, aspirations, and concerns of us evolutionarily-evolved human beings. Purpose, meaning, and value are therefore gifts of evolutionary nature, not of any supernatural or non-natural principle, presence, or power.